Fit for 55? An assessment of the effectiveness of the EU COM's reform proposal for the EU ETS - Theresa Wildgrube (Institute of Energy Economics at the University of Cologne (EWI), 2022)
To achieve the EU's new climate target of reducing emissions by at least 55% until 2030, the European Commission proposed a reform of the EU ETS in its 'Fit for 55' legislative package. The reform entails an increase of the linear reduction factor (LRF), an adjustment of the intake rules for the Market Stability Reserve (MSR) and the introduction of a fixed threshold for the cancellation of allowances. A numerical discrete-time optimization model of the EU ETS assesses the impact of the reform as a whole and decomposes this impact into the effects caused by the three individual reform elements. The results show a significant impact of the reform with 48% higher prices in 2021 compared to the current regulation. Among other factors, the reform proposal has thereby significantly driven the observed price increase in 2021. The impact of the increased LRF is substantial, while the adjustments of MSR and Cancellation Mechanism are less important. While the proposed reform strengthens the EU ETS, the increased LRF and the adjusted MSR rules do not fully achieve their intended goals. The increased LRF may not reach the intended emissions reduction of 61% for emissions covered under the EU ETS. The adjusted MSR regulation may increase resilience to shocks. Yet, it may also decrease MSR intake, reducing the MSR's ability to regulate allowance supply. The fixed cancellation threshold increases the predictability of the mechanism as intended. However, the changed cancellation volume has repercussions on the achievement of the emission reduction target.
Keywords: C61; D25; Q48; Q54; Q58; 330; Fit for 55; EU ETS; Linear reduction factor; Market Stability Reserve; Cancellation Mechanism